2017
DOI: 10.18632/oncotarget.14463
|View full text |Cite|
|
Sign up to set email alerts
|

The combination effect of homoharringtonine and ibrutinib on FLT3-ITD mutant acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a highly heterogeneous disease and internal tandem duplication mutation in FMS-like tyrosine-kinase-3 (FLT3-ITD) has a negative impact on outcome. Finding effective treatment regimens is desperately needed. In this study, we explored the inhibitory effect and mechanism of homoharringtonine (HHT) in combination with ibrutinib on FLT3-ITD mutant AML cells. Consequently, we observed a synergistic inhibitory effect when ibrutinib was combined with HHT to inhibit cell proliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Since this drug does not target specific proteins, its success is mainly due to the fact that it can disturb proteins with rapid turnover such as the leukemic cells’ upregulated short-lived oncoproteins BCR-ABL1 and antiapoptotic proteins (Mcl-1, Myc) leading to cells apoptosis [ 71 ]. Recently, other mechanisms indicated that it could also affect signaling pathways, like the Jak-stat5 pathway, by regulating protein tyrosine kinase phosphorylation [ 72 ] and by activating the TGF-β pathway through phosphorylation of smad3 [ 73 ].…”
Section: Secondary Metabolites From Plants As Anticancer Agentsmentioning
confidence: 99%
“…Since this drug does not target specific proteins, its success is mainly due to the fact that it can disturb proteins with rapid turnover such as the leukemic cells’ upregulated short-lived oncoproteins BCR-ABL1 and antiapoptotic proteins (Mcl-1, Myc) leading to cells apoptosis [ 71 ]. Recently, other mechanisms indicated that it could also affect signaling pathways, like the Jak-stat5 pathway, by regulating protein tyrosine kinase phosphorylation [ 72 ] and by activating the TGF-β pathway through phosphorylation of smad3 [ 73 ].…”
Section: Secondary Metabolites From Plants As Anticancer Agentsmentioning
confidence: 99%
“…P53 and p21 are important tumor suppressor proteins, and p53 induces the expression of p21 [10]. HHT has been shown to enhance p53/p21 expression in FLT3-ITD mutant AML [11], but this effect in LSCs and the consequence for cell proliferation are not well understood. Moreover, p53/p21 expression is induced by Notch ligand in myeloid lineage cells overexpressing Notch/Hes1 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although FLT3 tyrosine kinase inhibitors (TKI) have been developed to treat FLT3 -mutant AML patients, limited efficacy was observed because of relapse and rapid drug resistance [27]. Recently, we and others observed that HHT behaved a sensitive cytotoxic effect on FLT3 -ITD (+) AML cells [28], [29]. As many works highlighted, Hsp90 is a molecular chaperone of mutant FLT3 which is involved in holding conformation, stabilization and function of oncoproteins.…”
Section: Discussionmentioning
confidence: 99%